Free convection flow of power law fluid in a vertical cylinder of finite height - Que, Nguyen Van (Vietnam Journal of Mechanics, 1995)
A numerical solution has been presented for free convection flow of power law fluid in a vertical cylinder of finite height. The average velocity along the channel and the heat transfer have been calculated. Graphs of velocities and temperature are shown. The results show good agreement with analytic one in the asymptotic case.